2005
DOI: 10.1016/j.scitotenv.2004.12.084
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of cadmium and lead deposition on and adjacent to National Park Service lands in the vicinity of Red Dog Mine, Alaska

Abstract: Heavy metal escapement associated with ore trucks is known to occur along the DeLong Mountain Regional Transportation System (DMTS) haul road corridor in Cape Krusenstern National Monument, northwest Alaska. Heavy metal concentrations in Hylocomium splendens moss (n = 226) were used in geostatistical models to predict the extent and pattern of atmospheric deposition of Cd and Pb on Monument lands. A stratified grid-based sample design was used with more intensive sampling near mine-related activity areas. Spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 22 publications
1
77
0
Order By: Relevance
“…Some systems rely on single species indicators, for example, the plant Astragalus racemosus for selenium concentration (Trelease and 40 Trelease, 1938) and the bryophyte Hylocomium splendens for heavy metal pollution (Hasselbach et al, 2005). However, the majority of indicator systems use community-based approaches whereby the presence (and sometimes abundance) of multiple species is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Some systems rely on single species indicators, for example, the plant Astragalus racemosus for selenium concentration (Trelease and 40 Trelease, 1938) and the bryophyte Hylocomium splendens for heavy metal pollution (Hasselbach et al, 2005). However, the majority of indicator systems use community-based approaches whereby the presence (and sometimes abundance) of multiple species is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The haul road is the primary component of the Delong Mountain Regional Transportation System (DMTS) that also includes the mine and port facilities (Fig. 1); it traverses 32 km of CAKR land, for which a 100-year transportation easement was granted in 1985 by Congressional approval (Hasselbach et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moss sampled along the haul road corridor in 2000 contained elevated concentrations of cadmium (Cd), Pb, and Zn the source of which was attributed to escape of ore concentrate from trucks during transport (Ford and Hasselbach 2001). In a followup study, heavy metal concentrations in moss were measured throughout CAKR (n = 226) and geostatistical models were used to predict the extent and pattern of atmospheric deposition of Cd and Pb on NPS lands (Hasselbach et al 2005). Spatial regression analyses indicated that heavy metal deposition decreased with distance from the haul road and the port site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue concentrations of Pb were previously determined in mosses 1 collected from 24 sites across Arctic Alaska [65]; from multiple 1600-m transects lying perpendicular to a lead-zinc mine haul road and from nearby reference sites [141,142] in Cape Krusenstern National Monument-one of the NPS western Arctic management areas-and finally at Denali National Park and Preserve located in Interior Alaska [107]. Notably, moss samples of the latter study were washed before analysis, but washing was not done with the other studies.…”
mentioning
confidence: 99%